ANALYSIS OF LEGAL MECHANISMS ENSURING INFORMATION SECURITY OF THE INFORMATION INFRASTRUCTURE OF THE EUROPEAN UNION - DRYHA, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the analysis of international experience in the field of ensuring information security, in particular the activities of such international organizations as the UN, the Council of Europe and the European Union. Legislative acts and resolutions regulating issues of information security, cybercrime and protection of human rights in the information space were considered. The main focus is on the development of legal regulation within the EU, including the NIS Directive and its update NIS 2, which define cybersecurity standards for member states. The issue of integration of international norms into the national legislation of individual states is highlighted separately.Special emphasis is placed on the importance of the Universal Declaration of Human Rights (1948) and the Convention for the Protection of Human Rights and Fundamental Freedoms (1950) for the formation of international legal regulation of information security. The article covers the analysis of international legal documents aimed at combating cybercrime, including the Council of Europe Convention on Computer Information Crime and EU Directive 2016/1148. Modern initiatives and measures of the EU in the field of cyber security are described, in particular, the introduction of the NIS 2 Directive, which establishes strict requirements for ensuring network security and interaction of member states.Global challenges related to information security are highlighted, including the growth of cybercrime - cybercriminals use increasingly sophisticated methods to attack government institutions, businesses, and critical infrastructure, which calls for increased international cooperation.It was determined that the main principles of legislative regulation of social relations in the field of information security are formulated in the main international documents and, as their analysis shows, are generally recognized and prioritized in the development of information legislation for Ukraine.
Keywords: information; information security; information infrastructure; national security; information threats; information systems; Internet; European Union (EU); United Nations (UN); Council of Europe